Assessing Service Quality and Tourist Satisfaction in Labuan Bajo Tourism - I Nengah Dasi Astawa; Reynaldo Angga Siagian; Ni Wayan Noviana Safitri; Akib Hehanussa; Andriano Calrinto Mami (BIP's JURNAL BISNIS PERSPEKTIF, 2026)
This study examines the implementation of quality tourism and its relationship with tourist satisfaction in an emerging destination, focusing on tourism in Labuan Bajo, Indonesia. As a rapidly developing tourism destination, Labuan Bajo has been positioned as a strategic area that integrates natural attractions, tourism infrastructure, and sustainability-oriented development. However, empirical evidence on how quality tourism is perceived by visitors in emerging destinations remains limited. A quantitative descriptive approach was employed using a structured questionnaire with a five-point Likert scale. The study involved 200 respondents representing various stakeholders, including tourists, government, business actors, academics, and media. The analysis covered key dimensions of quality tourism, namely attractions, activities, amenities, accessibility, sustainability, environmental conditions, marketing, services, occupational health and safety, and overall tourist experience. The findings reveal that overall tourist satisfaction is categorized as very high, with an average score of 4.41. Natural attractions and service quality are identified as the main strengths of the destination. However, several aspects, including activity diversity, supporting facilities, accessibility for vulnerable groups, and community involvement, still require improvement. These results indicate that while Labuan Bajo has successfully delivered a positive tourism experience, further efforts are needed to enhance inclusiveness and long-term sustainability. This study provides empirical insights into quality tourism in emerging destinations and offers practical implications for destination managers and policymakers in improving tourism quality and competitiveness.